Diseño y construcción de una máquina de disco de diamante cortadora de neumáticos fuera de uso, en el recinto “Las cucharas” del cantón El Empalme, provincia del Guayas, año 2014 - Quintanilla Salcedo, Jinson David (2014)
In the present work we have designed and built a cutting machine out of use tires parallel to the tread, in order to reduce the physical effort of the operator time and improve cut quality with respect to which it obtains manually, and will reduce pollution hence the space they occupy in the environment, as these will be reused mainly in the cultivation of fruit pitahaya. Using a suitable alternative methodology for the design and construction of major systems, the machine was selected considering several criteria essential. The cutting process was developed by considering a diamond disk drive system of the double pinion gear, so that the tire enter into circular motion through-cutting rotor system driven by a motor, the cutting also has a lever and a hydraulic jack, the same drilling necessary to allow the acquisition of the two cut tire covers. The two tapas acquired by the cutting process will name as tire frame. ...